A consumer satisfaction model based on the integration of EDT and TAM: Comparative study of Korean and US consumers. Issue 5 (13th November 2017) - Cho, Yunjin
Abstract : Purpose: The purpose of this paper is to examine the process of consumer satisfaction formation for e-commerce. The study also predicts that the satisfaction formation model of e-commerce will differ between the US and Korean consumers due to differences in cultural background. Design/methodology/approach: The study integrates the expectation disconfirmation theory (EDT) and the technology acceptance model (TAM). The hypotheses are examined by analyzing a structural equation model for consumers in the USA and Korea. Findings: The results show that the model demonstrates good fit for both groups. For consumers in both countries, when purchasing fashion products on a new e-commerce site, the performance of the site's usefulness was found to be a crucial variable in their satisfaction and intention to use the site. While there was no significant difference in the multiple group measurement model invariance test, the findings are meaningful because the slight differences in the standard coefficients of the two groups are considered. Originality/value: It is meaningful to apply EDT and the TAM to the daily deal site environment. The influence of related variables can be reconfirmed and new consumer behaviors can be better understood. The research provides fresh insights into consumer behavior that can benefit managers when they make decisions in the e-commerce field.